2011
DOI: 10.1200/jco.2010.30.2554
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetics of Adult Acute Myeloid Leukemia: Prognostic and Therapeutic Implications

Abstract: Molecular analyses of leukemic blasts from patients with acute myeloid leukemia (AML) have revealed a striking heterogeneity with regard to the presence of acquired gene mutations and changes in gene and microRNA expression. Multiple submicroscopic genetic alterations with prognostic significance have been discovered. Application of gene- and microRNA profiling has identified genome-wide expression signatures that separate cytogenetic and molecular subsets of patients with AML into previously unrecognized biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
422
0
14

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 519 publications
(439 citation statements)
references
References 78 publications
3
422
0
14
Order By: Relevance
“…11 Similarly, CN-AML patients with double CEBPA mutations may not require allogeneic hematopoietic stem cell transplantation in first CR, but the lack of transplantation benefit has not been substantiated by data for these patients. 7 We showed that DNMT3A mutations provide additional prognostic information to better classify patients with CN-AML and, accordingly, may further improve consolidation treatment stratification in this subset of AML. Whether CN-AML patients with the favorable genotypes NPM1 mutated/FLT3-ITD negative or double CEBPA mutated but a simultaneous DNMT3A mutation may benefit from allogeneic hematopoietic stem cell transplantation in first CR is a question that will need to be addressed in future studies using larger patient cohorts.…”
Section: Discussionmentioning
confidence: 77%
“…11 Similarly, CN-AML patients with double CEBPA mutations may not require allogeneic hematopoietic stem cell transplantation in first CR, but the lack of transplantation benefit has not been substantiated by data for these patients. 7 We showed that DNMT3A mutations provide additional prognostic information to better classify patients with CN-AML and, accordingly, may further improve consolidation treatment stratification in this subset of AML. Whether CN-AML patients with the favorable genotypes NPM1 mutated/FLT3-ITD negative or double CEBPA mutated but a simultaneous DNMT3A mutation may benefit from allogeneic hematopoietic stem cell transplantation in first CR is a question that will need to be addressed in future studies using larger patient cohorts.…”
Section: Discussionmentioning
confidence: 77%
“…FLT3-ITD emerged as a biomarker of response to MTH FD2 suppression at the intersection of an shRNA screen and in silico query of genome-wide expression profiling of primary patient AML cells. FLT3-ITD is a gain-of-function mutation and is one of the most common alterations in AML, accounting for ∼20% of adult AML (Marcucci et al, 2011). AML with FLT3-ITD is characterized by higher rates of relapse, leading to poor overall survival of as low as 25% (Thiede et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Knockin mouse models have shown that FLT3 ITD causes suppression of lymphoid differentiation and increased proliferation of myeloid progenitors leading to a myeloproliferative phenotype without progression to AML. 14,15 Clinical data demonstrate CEBPA mutations as a reoccurring partner in AML with FLT3 ITD.…”
Section: Introductionmentioning
confidence: 99%